'Cuban Europe'? Greek and Iberian tiersmondisme in the 'Long 1960s'. (July 2015) - Kornetis, Kostis
This article addresses the ways in which the Third World emerged as a new referent in Greece and Spain in the 'long 1960s'. It shows how 'Thirdworldism' emerged out of growing dissatisfaction with the Old Left's defeatism and the ways in which, by way of the Cuban and Vietnamese example, radicals started to conceive their countries as US colonies. It also compares the ways in which Greek and Iberian Jacobins – some of whom came together in Paris after May '68 – formed a radical student diaspora. Examining the impact of extra-European anti-imperialist violence on the discourse and action of the most radical organizations that espoused the 'armed struggle' in both countries, the article shows that whereas Greek militants used violence only symbolically, their counterparts in Spain went all the way. The article finishes with the espousal of thirdworldist rhetoric by a new student generation in Greece leading to the mass uprising of November 1973, and a brief look at the afterlives of ETA and PAK, two of the most vocal exponents of this tendency, after the demise of the respective authoritarian regimes.